Leadership and good governance practices in the public sector: The case of district administration in Cambodia - Samnang Ouk; Sarom Mok; Sarin Chey (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The lack of leadership research in the public sector has left a gap in the literature. Sub-national administrations in Cambodia struggle with leadership in governance; even after reforms in 1993, the nation still lacks sound governance and the corresponding socioeconomic development. The fundamental purpose of this qualitative case study was to investigate an ethical leadership paradigm and determine whether it may inspire and sustain good governance in district administrations in Cambodia. The design of a case study aids in understanding complex social phenomena, particularly the nature of the case under consideration, and in producing knowledge about an individual, a group, and an organization. The theoretical frameworks for this study included utilitarian, deontological, and virtue ethics theories. The research focused on how Cambodian district administration officials worked to promote and sustain good governance through ethical leadership. Face-to-face interviews with open-ended questions were conducted with 25 district administration officials (DAOs), carefully selected from the target district administration. The data were analyzed by identifying themes through constant comparison, including honesty, concern for people, citizen engagement, accountability, transparency, and the rule of law. The results showed Honesty, concern for people, ethics infrastructure, ethics training, public involvement, access to information, openness, responsibility, rule of law, competency, and autonomy were among the main themes. Most participants said leaders were dishonest (88%) and indifferent about the general good (80%). All DAOs ranked ethics infrastructure, information availability, transparency, accountability, and the rule of law as top priorities (100%). Competency was rated well (88%). Ethics training (32%) and autonomy (16%) were less commonly mentioned, but they were nevertheless acknowledged as significant enabling characteristics. Ethical leadership has the potential to improve good governance in Cambodia’s district administration system and throughout the administrative hierarchy.